Utilización del transporte férreo para la competitividad y el desarrollo regional de Colombia: estudio caso de ruta Bogotá- Belencito Boyacá (2017)
Boyacá is an agricultural department, which has all the thermal floors which It has an optimum soil to develop this activity. We find That part of the 79% of agricultural production belongs to the family type according to the Center for the Learning of Finance and Rural Investment (CAFIR). This department in the agricultural sector has comparative advantages Competitive, but at the same time these are limited by the Logistic and technical deficiencies that it presents, so an inventory of The productive potential of the department, in order to establish Policy proposals that will lead the industry to improve these shortcomings in order to That it is more productive, efficient and competitive, without ignoring the Heterogeneity and diversity that characterizes this department.